Evaluating the antifracture efficacy of bisphosphonates. - Pazianas, M; Epstein, S; Zaidi, M (2009)
Oral bisphosphonate dosing schedules have evolved from the original daily regimens to weekly (alendronate and risedronate) and monthly (risedronate and ibandronate) regimens. Intravenous (i.v.) bisphosphonates are administered less frequently-quarterly ibandronate injection and yearly zoledronic acid i.v. infusion. Comparative fracture efficacy among BP options is increasingly a focus of debate. The approved daily oral BPs and annual zoledronic acid infusion demonstrated vertebral fracture prevention in clinical trials; however, nonvertebral fracture prevention results varied. Nondaily regimens of licensed agents (except for zoledronic acid) were approved via "bridging trials", which compared changes in bone mineral density and bone turnover markers with the approved daily regimen and generally collected fractures as adverse events. Head-to-head antifracture efficacy trials directly comparing available BPs are unlikely because the required sample sizes, durations and costs would be prohibitively large. Observational studies and the concept of annual cumulative exposure, used recently to evaluate the efficacy of nondaily ibandronate regimens, provide alternative methods to compare BP efficacy. At this time, the available trial and meta-analysis evidence supports effective reduction of vertebral fractures and NVFs with all approved BP regimens. This article presents a comprehensive review of the key efficacy data for currently available BPs, including their nondaily regimens, to assist clinicians in assessing treatment options for NVF prevention.